PENENTUAN SUATU PENGONTROL DENGAN INDEKS PERFORMANSI BERUPA NORMA CAMPURAN DAN - Soelistyo, Robertus Heri (MATEMATIKA, 2007)
﻿﻿﻿﻿. This paper considers the mix-norm / standard problem. Specifically an LQG control design problem involving a constraint on disturbance attenuation is addressed. It is shown that the / dynamic compensator gains are completely characterized via coupled Riccati/Lyapunov equation. The principle result involves sufficient condition for characterizing full order guaranteeing closed loop stability, constrained disturbance attenuation and an optimized performance bound.